2005
DOI: 10.1074/jbc.m412451200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Invasion Regulatory Domain within the Core Protein of Syndecan-1

Abstract: Among the four members of the syndecan family there exists a high level of divergence in the ectodomain core protein sequence. This has led to speculation that these core proteins bear important functional domains. However, there is little information regarding these functions, and thus far, the biological activity of syndecans has been attributed largely to their heparan sulfate chains. We have previously demonstrated that cell surface syndecan-1 inhibits invasion of tumor cells into three-dimensional gels co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
0
35
0
3
Order By: Relevance
“…This capture requires the region between amino acids 210 -236, with the C-terminal gln-gly-ala-thr 240 shown to be important in the HER2/␣3␤1 mechanism not required; in contrast, the pro-valasp 236 motif that is not necessary for capture of HER2 or ␣3␤1 integrin is required for the VLA-4/VEGFR2 mechanism. Prior work has also implicated the ala-val-val-ala-val 225 motif within this sequence as an inhibitory rather than stimulatory sequence during the invasion of type I collagen gels by human ARH-77 myeloma cells, although the receptors involved in this mechanism were not identified (40).…”
Section: -240mentioning
confidence: 99%
“…This capture requires the region between amino acids 210 -236, with the C-terminal gln-gly-ala-thr 240 shown to be important in the HER2/␣3␤1 mechanism not required; in contrast, the pro-valasp 236 motif that is not necessary for capture of HER2 or ␣3␤1 integrin is required for the VLA-4/VEGFR2 mechanism. Prior work has also implicated the ala-val-val-ala-val 225 motif within this sequence as an inhibitory rather than stimulatory sequence during the invasion of type I collagen gels by human ARH-77 myeloma cells, although the receptors involved in this mechanism were not identified (40).…”
Section: -240mentioning
confidence: 99%
“…The mechanism of Sdc1 action is unknown, but these activities are mediated by its ectodomain, which may help to cluster the integrin or recruit it into an active signaling complex with the ligand. A different region of the Sdc1 ectodomain has been shown to inhibit invasion of B lymphoid ARH-77 cells into collagen gels (Liu et al, 1998;Langford et al, 2005), but again the mechanism is not understood. These different Sdc1 activities vary in their dependence on HS chains, which are not required to stimulate ␣v␤3 signaling but are needed in the other two cases (Couchman, 2003;Beauvais et al, 2004;McQuade et al, 2006).…”
Section: Cell Adhesion and Invasionmentioning
confidence: 99%
“…52 Insight into sdc1 and cancer was obtained by Langford et al who showed that, in a short sequence of five amino acids (AVAAV) in the sdc1 ectodomain, only 26 amino acids from the transmembrane domain were responsible for the ability of intact sdc1 to inhibit tumor cell invasion. 53 Mutation in this site, called the invasion regulatory domain (IRD), permitted tumor cell invasion but did not impact the cell adhesion and spreading functions of sdc1. As discussed in ''The shedding of the ectodomain'' heading, and shown in Fig.…”
mentioning
confidence: 99%